Educational experiences as fields of influence in physics : an exploration of the critical incidents in student education - Holmes, Alexandra Jane (University of Sussex, 2015)
The purpose of this thesis is to explore the field of influences on the occupational trajectories of physics graduates in the United Kingdom. My research examines the assumptions by government and policy makers that school education holds the key to providing more physicists available for employment in physics-related occupations. The research analyses qualitative data from current and recently graduated students to explore the field of influences on their decisions to take physics, and how these experiences influence their identity as a scientist. My hypothesis tests these assumptions by examining the significant events, or critical incidents, during the educational experience on a physics degree. The research design is a case study of the physics departments of two UK institutions. A series of interviews provides insight into the educational journeys of current and recently graduated physics students and the consequent analysis identifies emergent themes. These themes include how the influences of school education and social and individual expectations engage people into enrolling on a physics degree. Further analysis explores how events occurring on the degree courses may influence occupational trajectories. My findings identify attitudes to laboratory work and institutional feedback as significant influences to this sample of individuals during their degree experience. This work has implications for highlighting the significance of laboratory work in future science education policies, as well as contributing to the extant research on STEM education.